React Strategy Instruction Enriched with Inquiry-Based Experiments: Exploring Middle School Students’ Understanding of Mixtures - Ayfer Mutlu (Universitas Pendidikan Indonesia, 2023)
This study investigates the effectiveness of using a REACT strategy instruction enriched with guided inquiry-based experiments to improve 7th-grade students’ understanding of mixtures compared to conventional teacher-centered instruction. A convergent parallel mixed-method design was used, and 39 middle school students were divided into experimental (N = 19) and control (N = 20) groups. In the experimental group, REACT strategy instruction, whose experimenting stage was implemented using inquiry-based experiments, was carried out. In the control group, conventional teacher-centered instruction was conducted. Four concept cartoons were used for data collection. In addition to quantitative analyses, individual profile maps were drawn, and students’ explanations in the “Because” section of the concept cartoons were analyzed to gain deeper insight into students’ conceptual change. According to the results, a REACT strategy instruction enriched with guided inquiry-based experience effectively improves 7th-grade students’ understanding of mixtures and rectifies misconceptions compared to conventional teacher-centered instruction. Based on the results of the study, it can be recommended to use the REACT strategy teaching model enriched with inquiry-based experiments for remedying students’ misconceptions and to use concept cartoons not only as a learning strategy but also as a tool for data collection, which will enable better evaluation of students’ misconceptions.